2011
DOI: 10.1128/jcm.01291-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing for Trichomonas vaginalis in Women: Results from a Prospective U.S. Clinical Trial

Abstract: Trichomoniasis is a common sexually transmitted disease associated with preterm birth, low birth weight, and increased susceptibility to infection with other pathogenic sexually transmitted microorganisms. Nucleic acid amplification tests for Trichomonas vaginalis have improved sensitivity for detecting infected individuals compared to existing culture-based methods. This prospective, multicenter U.S. clinical trial evaluated the performance of the automated Aptima T. vaginalis assay for detecting T. vaginalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 20 publications
(26 reference statements)
2
101
0
8
Order By: Relevance
“…Although the overall prevalence of T. vaginalis in women was approximately 10 to 15% less in this subacute care demographic compared to emergent care populations (16,23,24), significant T. vaginalis detection rates in both males and females (Table 2), as well as statistically increased T. vaginalis detection rates over those of C. trachomatis and N. gonorrhoeae provide evidence supporting consistent molecular screening for this agent. Indeed, appreciable T. vaginalis detection rates have been demonstrated in both symptomatic and asymptomatic populations (25,27,28). …”
Section: Discussionmentioning
confidence: 99%
“…Although the overall prevalence of T. vaginalis in women was approximately 10 to 15% less in this subacute care demographic compared to emergent care populations (16,23,24), significant T. vaginalis detection rates in both males and females (Table 2), as well as statistically increased T. vaginalis detection rates over those of C. trachomatis and N. gonorrhoeae provide evidence supporting consistent molecular screening for this agent. Indeed, appreciable T. vaginalis detection rates have been demonstrated in both symptomatic and asymptomatic populations (25,27,28). …”
Section: Discussionmentioning
confidence: 99%
“…Sample types include urine, clinician-collected vaginal swabs (CVS), endocervical swabs (ES), and PreservCyt solution (Hologic Incorporated, Bedford, MA) for liquid-based cytology (PCyt). A multicenter study that determined ATV performance for FDA clearance demonstrated that assay sensitivity ranged from 95.2% for urine to 100% for CVS, ES, and PCyt samples (28). ATV was highly specific for T. vaginalis (Ն98.9%) (28).…”
mentioning
confidence: 99%
“…However, this method has poor sensitivity, as the organism is reportedly detected in only 60%-70% of cases (104 ). The gold standard for detection of T. vaginalis, molecular testing by NAAT, has reported sensitivity and specificity of 95%-100% (105,106 ). FDA-cleared NAAT assays are available that test vaginal, cervical, or urine specimens from women and, recently, urine specimens from men.…”
Section: Trichomonas Vaginalismentioning
confidence: 99%